Liver damage in patients living with HIV on antiretroviral treatment with normal baseline liver function and without HBV/HCV infection: an 11-year retrospective cohort study in Guangxi, China - Jun Yu; Hao Liang; Fengxiang Qin; Junjun Jiang; Chunwei Qin; Yunxuan Huang; Bingyu Liang; Yuexiang Xu; Jiegang Huang; Zhiliang Xu; Chuanyi Ning; Yanyan Liao; et al. (BMJ Open)
Objective To characterise the association between duration of exposure to antiretroviral treatment (ART) and liver damage in HIV patients with an initially normal baseline liver function and without hepatitis B virus (HBV)/hepatitis C virus (HCV) infection.Methods A retrospective cohort study was conducted in HIV-infected individuals with normal liver function parameters at ART initiation and without HBV/HCV infection, from 14 April 2004 to 13 April 2015 in Guigang city, Guangxi, China. The association between duration of ART and liver damage (grade II–IV liver enzyme elevation [LEE] and/or total bilirubin elevation [TBE]), was analysed. Cox regression was used to examine the factors related to liver damage.Results Of 2119 eligible patients, 12.41% (263/2119) developed liver damage (grade II–IV LEE/TBE) and contributed 4.11/100 person-years crude incidence rate. The highest liver damage incidence was observed in patients with 6–12 months’ ART (15.16/100 person-years). The incidence decreased to 5.56/100 person-years in patients with 12–18 months’ ART and 3.13/100 person years in patients with 18–24 months’ ART, and then maintained at a relatively low and stable level in patients with 2 years’ ART or longer (average of 3.65/100 person-years). Cox regression analysis revealed that current WHO disease stage II, III or IV (compared with stage I) were the risk factors for liver damage, while baseline disease stage II, III (compared with stage I) and current regimen 3TC+AZT+NVP were the protective factors for liver damage.Conclusions Liver damage always exists among HIV-infected patients on ART with normal baseline liver function and without HBV/HCV infection. Nevertheless, cumulative ART duration does not increase the risk of liver damage. ART could tend to be long-term, however, monitoring and management of liver damage among patients on ART are also important in clinical therapy.